Necrotising cellulitis in an ex preterm neonate with group B streptococcal sepsis. - Mcdonald, F.; Abdelreheim, M.; Kerrison, C. (European Journal of Pediatric Dermatology, 2025)
It is well known that necrotic skin changes can occur with different microbial agents. However, there are very few reported cases of necrotic skin changes with Streptococcus B infection, of which all appear to be in patients with underlying immunodeficiencies. Here we present the case of a 6-week-old girl, who presented to hospital with necrotic skin changes to the occipital area of her head and whose blood cultures later grew Group B Streptococcus.